Environmental Factors of Sleep Hygiene That Influence The Level of Pain on Criticall ill Patients in Intensive Care Unit - Heru Suwardianto; Dyah Ayu Kartika Wulan Sari (Universitas STRADA Indonesia, 2020)
The study population was all patients in the ICU. Samples were 170 patients in the ICU according to the inclusion criteria. Independent variables are room temperature, lighting level, and noise level. The dependent variable is the level of pain. The research instruments were CPOT, lux meter, and light meter. Data were collected using observation sheets and analyzed using regression. Result of research showed that the pain scale based on CPOT most respondents had Moderate pain as many as 43 respondents (50.6%), that the lighting environment (40.22 ± 41.1), noise (60.23 ± 8.5), and room temperature (26.76 ± 1.2) were not directly related to the patient's pain level. Environments factors in this study were not directly related to the pain level. there may be other factors that cause the patient's pain to determine the action, prognosis, and use of a mechanical ventilator